EXPERIENCE-BASED STRATEGIC PLANNING BY OWNERS OF SMALL AND MEDIUM ENTERPRISES PRODUCING DOLPHIN CASSAVA CHIPS - Wisma Miftahur Rozi; Sudarmiatin Sudarmiatin; Puji Handayati; Naswan Suharsono (JURNAL PROFIT, 2025)
Strategic planning is an important element for the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in facing competition and market dynamics. This study aims to analyze the strategic planning process at Lumba-Lumba Cassava Chips MSME in Malang, which operates in the highly competitive snack food industry. The approach used is descriptive qualitative through case study method, with data collection techniques in the form of in-depth interviews, observation of production and marketing processes, and documentati . Data analysis was conducted using the Miles and Huberman model through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that strategic planning in this SME is carried out informally and based on the owner's experience, but it covers the main components of strategic planning, namely situation analysis, strategy formulation, implementation, and evaluation. The strategies are aimed at improving product quality, stabilizing raw material supplies, and expanding the marketing network through souvenir shops. However, product innovation, digital marketing, and strategy documentation are still not optimal. Strategy evaluation is also carried out intuitively without measurable performance indicators. This study concludes that although strategic planning at Lumba-Lumba Cassava Chips SME is not yet structured, the strategies implemented are able to maintain business sustainability. This study provides implications for SME actors to strengthen strategy documentation, product innovation, and digital marketing, as well as for SME facilitators to improve strategic management training in line with the SME context.